2020
DOI: 10.1103/physrevapplied.13.064004
|View full text |Cite
|
Sign up to set email alerts
|

Constructive Near-Field Interference Effect in a Birdcage MRI Coil with an Artificial Magnetic Shield

Abstract: Radio-frequency (rf) coils are used in all clinical and research magnetic-resonance-imaging (MRI) systems to excite nuclear spins and to receive signals from them. The quality of imaging depends strongly on the signal-to-noise ratio (SNR) and the transmit efficiency of the coils. The birdcage volume coils used in most MRI scanners for homogeneous imaging of a sample are typically shielded from the external systems of the MRI scanner, i.e., the gradient coils, to confine the rf field within the region of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In situations with weaker loading than described in this work (e.g., children in a 3 T scanner whole body birdcage, a head in a 400 mm birdcage at 7 T or small animal scanners [28]), this loading problem will be less severe. The energy can propagate in the azimuthal direction without too much losses, which results in a sinusoidal current pattern over the rungs.…”
Section: Discussion the Split Ring Shieldmentioning
confidence: 84%
See 2 more Smart Citations
“…In situations with weaker loading than described in this work (e.g., children in a 3 T scanner whole body birdcage, a head in a 400 mm birdcage at 7 T or small animal scanners [28]), this loading problem will be less severe. The energy can propagate in the azimuthal direction without too much losses, which results in a sinusoidal current pattern over the rungs.…”
Section: Discussion the Split Ring Shieldmentioning
confidence: 84%
“…Other studies [22][23][24][25][26] have demonstrated improved performance for local transmit antennas by using a magnetically conducting shield, but for the birdcage coil at 3 T, this has not been investigated. Lezhennikova et al [27,28] have investigated potential improvements of birdcage coils with a magnetic shield under weaker loading conditions, where no adaptation to the driving scheme is required. However, they have not investigated potential SAR hotspots in any scenario where tissue is present close to one of the conductors, which was the focus of this work.…”
Section: The 16tx Birdcage With Pmc Shield At 3 Teslamentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the structure in [22] provides more homogeneous B 1 field and lower electric field. In [23] it was shown that the artificial mag-125 netic shield realized as a miniaturized corrugated structure when used as a shied increases the efficiency of the preclinical birdcage coil and this improvement depends on the size of a conducting sample. The efficiency gain of 13% was numerically and experimentally demonstrated for MRI at 130 7 T for the artificial magnetic shield over a conventional copper shield.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, by using a corrugated shield one can improve the signal-to-noise ra-135 tio when using the same coil for the reception, but with the same homogeneity. However, since a small preclinical birdcage was considered, no analysis of SAR was made in [23].…”
Section: Introductionmentioning
confidence: 99%